2000
DOI: 10.1177/002215540004800614
|View full text |Cite
|
Sign up to set email alerts
|

Luminal Localization of Blood-Brain Barrier Sodium, Potassium Adenosine Triphosphatase Is Dependent on Fixation

Abstract: Cytochemical data in the literature reporting localization of sodium, potassium adenosine triphosphatase (Na(+), K(+)-ATPase) in the blood-brain barrier (BBB) have been contradictory. Whereas some studies showed the enzyme to be located exclusively on the abluminal endothelial plasma membrane, others demonstrated it on both the luminal and abluminal membranes. The influence of fixation on localization of the enzyme was not considered a critical factor, but our preliminary studies showed data to the contrary. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…However, even in these studies, because the assays were conducted after tissue fixation there is the ever present risk that Na + -pumps were inactivated prior to the assay [304, 313, 314]. Furthermore, it is conceivable that fixation might have affected the pumps in one membrane more than the other [311]. It should be noted that, using the K-NPPase cytochemical assay, differences in localization of the Na + -pumps were observed in the choroid plexus that have never been adequately explained [315].…”
Section: Ion and Fluid Transport At The Blood–brain Barriermentioning
confidence: 99%
See 2 more Smart Citations
“…However, even in these studies, because the assays were conducted after tissue fixation there is the ever present risk that Na + -pumps were inactivated prior to the assay [304, 313, 314]. Furthermore, it is conceivable that fixation might have affected the pumps in one membrane more than the other [311]. It should be noted that, using the K-NPPase cytochemical assay, differences in localization of the Na + -pumps were observed in the choroid plexus that have never been adequately explained [315].…”
Section: Ion and Fluid Transport At The Blood–brain Barriermentioning
confidence: 99%
“…levamisole. However, even so it is necessary to demonstrate that the activity detected requires the presence of K + and is inhibited by ouabain, usually at 1 mM.Manoonkitiwongsa et al [311] investigated the effects of a range of concentrations of formaldehyde and glutaraldehyde. They found that fixation with 2% formaldehyde yielded 1.5 as the ratio of the luminal to abluminal product densities but with 2% formaldehyde plus glutaraldehyde at 0.1, 0.25 or 0.5% the ratio decreased to 0.7, 0.5 or 0.4 [311].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There were both similarities and differences compared to tissues fi xed with 4% formaldehyde. The similarities were that reaction product was present at the BBB for all of these controls and the amount of reaction product on the abluminal surface of the endothelia ultrastructure is poor, because 4% formaldehyde is a weak fi xative, particularly compared to fi xatives containing even small amounts of glutaraldehyde (Manoonkitiwongsa et al 2000). Fig.…”
Section: Formaldehyde Control Groupsmentioning
confidence: 99%
“…The diffi culty with image analysis procedures is that it can be very tedious and time-consuming, which can discourage investigators from using quantitative measurements or even the incubation medium of Ando et al (1981) for the BBB or any other tissue. We have had this experience with previous quantitative studies of Na ϩ , K ϩ -ATPase reaction product in the BBB (Manoonkitiwongsa et al 2000).…”
Section: Need For Quantitative Analysis Of Reaction Product In Ca 2ϩ mentioning
confidence: 99%